2012
DOI: 10.1177/1090198112463393
|View full text |Cite
|
Sign up to set email alerts
|

The National Health Educator Job Analysis 2010

Abstract: The National Health Educator Job Analysis 2010 was conducted to update the competencies model for entry- and advanced-level health educators. Qualitative and quantitative methods were used. Structured interviews, focus groups, and a modified Delphi technique were implemented to engage 59 health educators from diverse work settings and experience levels in a seven-step instrument development process. An online survey was then completed by 1,022 practicing health educators. Survey participants used 4-point ordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 18 publications
4
41
1
Order By: Relevance
“…Consistent with prior research (Chaney et al, 2013;Doyle et al, 2012;Gambescia et al, 2009;Gilmore et al, 2005), results revealed that applied health education takes place in very varied work settings provided by individuals with diverse backgrounds, credentials, professional preparation, and job titles. In this context, one participant obtained a bachelor's degree in community health, previously worked at a fitness center, performed African dance for 12 years, and received a master's degree and a state-issued teaching license in health education, enabling her to serve as a high school health education at the time of the study.…”
Section: > > Discussionsupporting
confidence: 89%
“…Consistent with prior research (Chaney et al, 2013;Doyle et al, 2012;Gambescia et al, 2009;Gilmore et al, 2005), results revealed that applied health education takes place in very varied work settings provided by individuals with diverse backgrounds, credentials, professional preparation, and job titles. In this context, one participant obtained a bachelor's degree in community health, previously worked at a fitness center, performed African dance for 12 years, and received a master's degree and a state-issued teaching license in health education, enabling her to serve as a high school health education at the time of the study.…”
Section: > > Discussionsupporting
confidence: 89%
“…Building on CUP study approaches and analyses, in 2008 SOPHE, AAHE, and NCHEC conducted the National Health Educator Job Analysis, which surveyed 1,022 respondents from 49 states, the District of Columbia, and Puerto Rico. The result of the online survey was an updated model of responsibilities, competencies, and subcompetencies for health education specialists and the addition of 133 knowledge items (Doyle et al, 2012).…”
Section: Role Delineation Researchmentioning
confidence: 99%
“…The United States have a rich history of development of competencies for the health education profession [ 7 ]. They currently operate out of a model that is organized into seven areas of responsibility, further broken down into 34 competencies and then divided into 223 sub-competencies [ 8 ]. Since health promotion is delivered by different kinds of professionals in various settings, contextualising practitioner competencies is an important step in order to provide a framework for professional practice.…”
Section: Introductionmentioning
confidence: 99%